1985
DOI: 10.1021/ja00297a032
|View full text |Cite
|
Sign up to set email alerts
|

Regiospecific sulfonation of secondary hydroxyl groups of .alpha.-cyclodextrin. Its application to preparation of 2A2B, 2A2C-, and 2A2D-disulfonates

Abstract: Specific sulfonation on a secondary hydroxyl group (C-2-OH or C-3-OH) of -cyclodextrin was elucidated. A reaction of -cyclodextrin with m-nitrobenzenesulfonyl chloride exclusively gave the C-2-sulfonate, while /3-naphthalenesulfonyl chloride selectively afforded the C-3-sulfonate. The former reaction also gave selectively 2A2B-, 2A2C-, and 2A2D-disulfonates as the products of disulfonation. They were well separated by reversed-phase column chromatography, isolated, and converted to corresponding di-manno-epoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 0 publications
1
34
0
1
Order By: Relevance
“…In contrast, heterobifunctionalized CDs have been prepared via multistep synthesis (depending on the steric hindrance of the moiety on the CD scaffold and on the bulkiness of reagents [ 22 ]) or by modification of homobifunctionalized CDs [ 23 24 ]. These and previous studies [ 25 26 ] confirmed that CD derivatives with bulky substituents such as tosyl groups can be separated by reversed-phase column chromatography and HPLC separation methods can be easily scaled up to obtain grams of pure regioisomers. However, to the best of our knowledge, no such comparative regiochemical study of homobifunctionalized α-CDs prepared from the most commonly used CD intermediates has been conducted thus far although the regioisomer pattern of these intermediates is crucial for the investigation of new single isomer CDs with reproducible and definite structures.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…In contrast, heterobifunctionalized CDs have been prepared via multistep synthesis (depending on the steric hindrance of the moiety on the CD scaffold and on the bulkiness of reagents [ 22 ]) or by modification of homobifunctionalized CDs [ 23 24 ]. These and previous studies [ 25 26 ] confirmed that CD derivatives with bulky substituents such as tosyl groups can be separated by reversed-phase column chromatography and HPLC separation methods can be easily scaled up to obtain grams of pure regioisomers. However, to the best of our knowledge, no such comparative regiochemical study of homobifunctionalized α-CDs prepared from the most commonly used CD intermediates has been conducted thus far although the regioisomer pattern of these intermediates is crucial for the investigation of new single isomer CDs with reproducible and definite structures.…”
Section: Introductionsupporting
confidence: 63%
“…The synthetic approach started with the preparation of 6 A ,6 X -capped α-CD derivatives. From special capping agents previously used on α-CD [ 17 18 26 ], we selected the most common, relatively inexpensive and commercially available m -benzenedisulfonyl chloride and biphenyl-4,4´-disulfonyl chloride. The prepared 6 A ,6 X -disulfonyl-capped CDs 2 and 3 were immediately converted to the more stable 6 A ,6 X -diazido-α-CDs 4 to prevent hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, in contrast to functionalization of the primary face of cyclodextrins, which has been extensively studied, the chemistry available for functionalization of the secondary face is less well developed. Preparative methods for secondaryfunctionalized cyclodextrins generally involve moderate yields and purification of synthetic intermediates by reverse-phase chromatography, which is scale-limited (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Although, sulfonation of the secondary hydroxyl groups of the CyDs as precursors of functional CyDs has been reported to be more difficult. [13][14][15][16][17][18][19] Teranishi was prepared various sulfonyl CyDs at the C-2 position from sulfonyl imidazole using molecular sieves (4A), in which these procedures are conveniently succeeding under mild condition. [20][21][22][23] Therefore, it would be interesting to design a molecular sensory system of a new fluorescent CyD labeled at both the upper and lower rims.…”
mentioning
confidence: 99%